Anti-hyperlipidemic and antioxidant potentials of aqueous leaf extract of Telfairia occidentalis (fluted pumpkin) in male Sprague-Dawley rats (Nigerian Journal of Physiological Sciences, 2021)
In Africa traditional medicine, certain plant leaves are employed in the treatment of metabolic disorders such as dyslipidaemia. Telfairia occidentalis is named among Nigerian plants that are under investigation for anti-hyperlipidemic activity. The antihperlipidemic and antioxidant potentials of Telfairia Occidentalis (TO) aqueous leaf extract were studied in male Sprague- Dawley rats. Twenty-four healthy male Sprague-Dawley rats were grouped into four of six rats thus: Group A (control) received normal saline (10mg/Kg); treated groups B, C and D, received, 50mg/kg; 100mg/kg; and 150mg/kg of Telfairia occidentalis aqueous leaf extract for 14 days respectively. At the end of the experiment serum cholesterol (CHOL), triglyceride (TG), high density lipoprotein (HDL) and low density lipoprotein (LDL) were determined. Liver enzymes’ aspartate amino transferase (AST), alanine amino transferase (ALT), Alkaline phosphatase (ALP) were also assessed. Serum level creatinine was determined and antioxidant enzymes’ reduced glutathione (GSH), superoxide dismutase (SOD) and catalase (CAT) were investigated. Lipid peroxidation’s malonaldehyde (MDA) level was also assessed. Results from the current study showed a significant decrease in CHOL and LDL levels at all the doses tested (p